Regionalisms and Imperialisms in the making of the Russian Far East, 1903-1926 - Sablin, Ivan; Sukhan, Daniel (Slavic review, 2018)
Tracing the emergence of the Russian Far East as a new region of the Russian Empire, revolutionary Russia, and the Soviet Union through regionalist and imperialist discourses and policies, this article briefly discusses Russian expansion in the Pacific littoral, outlines the history of regionalism in North Asia during the revolutionary and early Soviet periods, and focuses on the activities of the Far Eastern Council of People's Commissars (Dal΄sovnarkom), the Far Eastern Republic (FER), and the Far Eastern Revolutionary Committee (Dal΄'revkom). Inspired by Siberian regionalism and other takes on post-imperial decentralization, the Bolshevik Aleksandr Mikhailovich Krasnoshchekov and other regional politicians became the makers of the new region from within. Meanwhile, the legacies of the empire's expansionism, the Bolshevik “new imperialism” in Asia, and the Japanese military presence in the region during the Russian Civil War accompanied the consolidation of the Russian Far East.
Gesehen am 27.05.2019